Cross-species single-nucleus analysis reveals the potential role of whole-genome duplication in the evolution of maize flower development - Huawei Feng; Wenjuan Fan; Min Liu; Jiaqian Huang; Bosheng Li; Qing Sang; Baoxing Song (BMC Genomics)
Abstract Background The evolution and development of flowers are biologically essential and of broad interest. Maize and sorghum have similar morphologies and phylogeny while harboring different inflorescence architecture. The difference in flower architecture between these two species is likely due to spatiotemporal gene expression regulation, and they are a good model for researching the evolution of flower development. Results In this study, we generated single nucleus and spatial RNA-seq data for maize ear, tassel, and sorghum inflorescence. By combining single nucleus and spatial transcriptome, we can track the spatial expression of single nucleus cluster marker genes and map single nucleus clusters to spatial positions. This ability provides great power to annotate the single nucleus clusters. Combining the cell cluster resolved transcriptome comparison with genome alignment, our analysis suggested that maize ear and tassel inflorescence diversity is associated with the maize-specific whole genome duplication. Taking sorghum as the outgroup, it is likely that the loss of gene expression profiling contributes to the inflorescence diversity between tassel and ear, resulting in the unisexual flower architecture of maize. The sequence of highly expressed genes in the tassel is more conserved than the highly expressed genes in the ear. Conclusion This study provides a high-resolution atlas of gene activity during inflorescence development and helps to unravel the potential evolution associated with the differentiation of the ear and tassel in maize.